Confronting Discrimination and Inequality in China Chinese and Canadian Perspectives - P. Mendes, Errol (University of Ottawa Press / Les Presses de l'Université d'Ottawa, 2009)
Confronting Discrimination and Inequality in China focuses on the most challenging areas of discrimination and inequality in China, including discrimination faced by HIV/AIDS afflicted individuals, rural populations, migrant workers, women, people with disabilities, and ethnic minorities. The Canadian contributors offer rich regional, national, and international perspectives on how constitutions, laws, policies, and practices, both in Canada and in other parts of the world, battle discrimination and the conflicts that rise out of it. The Chinese contributors include some of the most independent-minded scholars and practitioners in China. Their assessments of the challenges facing China in the areas of discrimination and inequality not only attest to their personal courage and intellectual freedom but also add an important perspective on this emerging superpower.